MICROBIAL LOAD AND EFFICAY OF ANTIMICROBIAL WIPES ON SHOPPING CART HANDLES, IN UNIAZAH CITY, ALQASSIM, K.S.A - Mohammad AL Felaiw, Amjad; Ali, Sarah (International Journal of Research -GRANTHAALAYAH, 2019)
Shopping carts are one of the most important tools for shopping in supermarkets. Shopping carts are used by hundreds of people each day and may be used 7 days per week and sometimes 24 hours per day. This study examined the amount of bacteria present on shopping cart handles before and after using antimicrobial wipes. 40 cart handles from 2 grocery stores in Uniazah city were swabbed. Cart handles were swabbed and then wiped with antimicrobial wipes and swabbed again and samples were transported to the laboratory. After incubation period of 24 hours at 37° C levels of bacteria were measured using a spectrophotometer with absorbency light at 686nm. 24 hours of incubation revealed that absorbency of swabs after antimicrobial wipes, on average was reduced to, about half, compared to, Swabs taken before, antimicrobial wipes. Also, the bacterial counts were less on the cart handles that wipe with antimicrobial wipes. It was concluded that the bacterial load, varied on the carts handles; and that the cart handles that were wiped with antimicrobial wipes had far less bacterial growth than the cart handles that were not wiped with antimicrobial wipes. Using antimicrobial wipes may be a way to reduce our exposure to harmful bacteria.